Model Kinerja Non Keuangan: Sinergitas Akuntansi Hijau dan Lingkungan - Prayitno, Hadi; Budiwitjaksono, Gideon Setyo; Priono, Hero (Gorontalo State University, 2026)
Hospitals, as public service institutions, have a responsibility to integrate environmental aspects into their managerial practices. This study analyzes the influence of green accounting and environmental performance on managerial performance at Rumah Sakit Mata Undaan Surabaya. Data were collected from 39 managerial-level respondents and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of SmartPLS 4.0 software. The results show that green accounting has a positive and significant effect on managerial performance, supporting the stakeholder theory perspective. In contrast, environmental performance has a negative but insignificant effect on managerial performance. These findings highlight the importance of strengthening sustainability strategies in hospital managerial decision-making to create long-term sustainable value.